Generation of a novel mouse strain with fibroblast-specific expression of Cre recombinase - Jahedul Alam; Moses Musiime; Andreas Romaine; Mugdha Sawant; Arne Olav Melleby; Ning Lu; Beate Eckes; Geir Christensen; Donald Gullberg (Matrix Biology Plus, 2020)
Cell-specific expression of genes offers the possibility to use their promoters to drive expression of Cre-recombinase, thereby allowing for detailed expression analysis using reporter gene systems, cell lineage tracing, conditional gene deletion, and cell ablation. In this context, current data suggest that the integrin α11 subunit has the potential to serve as a fibroblast biomarker in tissue regeneration and pathology, in particular in wound healing and in tissue- and tumor fibrosis. The mesenchyme-restricted expression pattern of integrin α11 thus prompted us to generate a novel ITGA11-driver Cre mouse strain using a ϕC31 integrase-mediated knock-in approach. In this transgenic mouse, the Cre recombinase is driven by regulatory promoter elements within the 3 kb segment of the human ITGA11 gene. β-Galactosidase staining of embryonic tissues obtained from a transgenic ITGA11-Cre mouse line crossed with Rosa 26R reporter mice (ITGA11-Cre;R26R) revealed ITGA11-driven Cre expression and activity in mesenchymal cells in a variety of mesenchymal tissues in a pattern reminiscent of endogenous α11 protein expression in mouse embryos. Interestingly, X-gal staining of mouse embryonic fibroblasts (MEFs) isolated from the ITGA11-Cre;R26R mice indicated heterogeneity in the MEF population. ITGA11-driven Cre activity was shown in approximately 60% of the MEFs, suggesting that the expression of integrin α11 could be exploited for isolation of different fibroblast populations. ITGA11-driven Cre expression was found to be low in adult mouse tissues but was induced in granulation tissue of excisional wounds and in fibrotic hearts following aortic banding. We predict that the ITGA11-Cre transgenic mouse strain described in this report will be a useful tool in matrix research for the deletion of genes in subsets of fibroblasts in the developing mouse and for determining the function of subsets of pro-fibrotic fibroblasts in tissue fibrosis and in different subsets of cancer-associated fibroblasts in the tumor microenvironment.